Parallel consulting method: student and tutor evaluation in general practice. Issue 5 (3rd September 2021) - Allan, Rachel; McAleer, Sean
ABSTRACT: The parallel consulting method (PCM) is widely used by general practitioners (GPs) for teaching medical students. Studies have described individual aspects of bedside teaching in community settings, including the logistics of using the PCM, but there has been no evaluation of it as a teaching method. This study aimed to evaluate the PCM and whether it helped students develop consultation, clinical and clinical reasoning skills. The study was based at the Oxford University Primary Care Department. Penultimate clinical year students (n = 63) were recruited to take part in this mixed methods study. Students completed a questionnaire with closed and open-ended questions rating the PCM. A focus group explored questionnaire themes. GP tutors completed a questionnaire about the PCM and the logistics of delivering it. Three tutors took part in semi-structured interviews. The PCM helped develop students' consulting, and clinical reasoning skills. Teaching was improved when tutors were unrushed and had increased time to provide feedback and teaching. Delivery logistics of the PCM impacted on whether tutors were rushed and found it difficult to teach. Most benefit was derived when students were well briefed with sufficient debriefing time following a consultation. The following steps are recommended for effective delivery of the PCM teaching model: ensure tutors are appropriately trained; comprehensively brief the student about how to gain the most out of the learning experience; plan the logistics; ensure appropriate review and debriefing following consultation; review clinical cases after the session teaching on any outstanding aspects.